SIMULATION MODELLING concepts, tools and practical business applications. - Greasley, Andrew ([S.l.] : ROUTLEDGE, 2022)
While simulation has a vast area of application, this textbook focuses on the use of simulation to analyse business processes. It provides an up-to-date coverage of all stages of the discrete-event simulation (DES) process, covering important areas such as conceptual modelling, modelling input data, verification and validation and simulation output analysis. The book is comprehensive yet uncomplicated, covering the theoretical aspects of the subject and the practical elements of a typical simulation project, demonstrated by cases, examples and exercises. It also shows how simulation relates to new developments in machine learning, big data analytics and conceptual modelling techniques. Guidance is provided on how to build DES models using the Arena, Simio and Simul8 simulation software, and tutorials for using the software are incorporated throughout. Simulation Modelling offers a uniquely practical and end-to-end overview of the subject, which makes it perfect required or recommended reading for advanced undergraduate and postgraduate students studying business simulation and simulation modelling as part of operations research, business analytics, supply chain management and computer science courses.
OCLC-licensed vendor bibliographic record.
Keywords: Business -- Data processing; Decision making -- Simulation methods; BUSINESS & ECONOMICS / Operations Research; COMPUTERS / Computer Simulation; BUSINESS & ECONOMICS / Decision-Making & Problem Solving